"It's Not Just About Getting Along": Exploring Learning Through the Discourse and Practice of Interprofessional Collaboration. (November 2020) - Martimianakis, Maria Athina (Tina); Fernando, Oshan; Schneider, Rayfel; Tse, Shirley; Mylopoulos, Maria
Abstract : Purpose: Interprofessional collaboration (IPC) is a necessary competency for all professionals. However, IPC can be fraught with politics leading to variable uptake and execution. The authors set out to understand how trainees come to appreciate the value of the "team" in their learning and to describe the type of learning related to IPC afforded to trainees in a highly collaborative complex care context. Method: The authors conducted 72 hours of observations of pediatric rheumatology settings at a large pediatric hospital across 18 months. They interviewed 10 health professionals and analyzed an archive of texts to ascertain how the field of pediatric rheumatology conceptualizes the role of IPC. They used the concept of governmentality and critical discourse analysis to describe how values of collaboration enabled learning and theories of expertise to understand how learning was enacted and perceived. Results: Collaboration was perceived to be a product of providing good rheumatological care, which in this case, aligned well with hospital model of IPC. This alignment afforded trainees learning opportunities beyond preparing them to get along with other health professionals. IPC, when role modeled during problem solving, created the conditions for learning "why" collaboration is important for clinical expertise. Conclusions: By critically examining the relationship between discourse, practice, and learning, the authors have described how practices that underpin collaboration as a clinical competency are distinct from collaboration as cultural work contributing to civility within teams and across the organization. Abstract : Supplemental Digital Content is available in the text.